2011
DOI: 10.1080/03079457.2011.606799
|View full text |Cite
|
Sign up to set email alerts
|

A critical review ofSalmonellaTyphimurium infection in laying hens

Abstract: Salmonella Typhimurium has been reported to contaminate egg production across the world, but where Salmonella Enteritidis is endemic it is this latter serovar that dominates egg-borne salmonellosis. However, Salmonella Typhimurium is a major food-borne pathogen so it is important to understand how it can impact the microbiological safety of eggs and what serovar-specific control strategies may be appropriate in the future as control over Salmonella Enteritidis continues to improve. To that end, the present rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 62 publications
(65 reference statements)
1
56
1
Order By: Relevance
“…The Australian poultry industry differs from most other countries in that Salmonella enterica serovar Enteriditis ( S . Enteriditis) is not endemic in chicken breeding and egg‐laying flocks 3, 4…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Australian poultry industry differs from most other countries in that Salmonella enterica serovar Enteriditis ( S . Enteriditis) is not endemic in chicken breeding and egg‐laying flocks 3, 4…”
mentioning
confidence: 99%
“…A review of Salmonella infection in laying hens noted that most studies conducted with Salmonella colonisation in chickens have been short term (2 weeks) and used single administration of very high infective doses and that this may not reflect the situation for the whole productive life of a commercial layer hen 4. It could be argued that if a vaccine merely lowers organism numbers compared with controls for a short period but natural decline in organism presence is essentially the same after approximately 2 weeks, the vaccine has not really achieved a long‐term improvement compared with no treatment.…”
mentioning
confidence: 99%
“…Other S. Typhimurium DTs, such as DT104 and DT49, can infect chickens and cause egg contamination Williams et al, 1998;Okamura et al, 2010). The virulence and invasiveness of S. Typhimurium are also determined by the bacterial strain (Barrow et al, 1987;Keller et al, 1997;Okamura et al, 2010;Wales and Davies, 2011). For example, a study investigating the invasiveness and egg contamination potential of 10 S. Typhimurium DT104 strains has shown that they differed in their ability to cause ovarian infection and egg contamination (Okamura et al, 2010).…”
Section: Factors Influencing Salmonella Pathogenesis In Chickensmentioning
confidence: 99%
“…The success of S. Enteritidis in the transovarian transmission route can be associated with the presence in this serovar of the SEF14 fimbriae (which might be involved in the colonization of the reproductive organs), the presence of the yafD gene (which is essential for resistance in the albumen), and with the lipopolysaccharide structure, a key factor in oviduct persistence and survival in egg albumen (Lu et al, 2003;Coward et al, 2013), particularly at a hen body temperature of 41.5 °C (Coward et al, 2013). S. Typhimurium is able to colonize ovaries and internally contaminate eggs (Okamura et al, 2001a;Wales and Davies, 2011;Martelli and Davies, 2012). Other Salmonella serovars are rarely isolated from egg contents, but can infect the hen reproductive organs (Okamura et al, 2001a;Gast et al, 2004;Martelli and Davies, 2012).…”
Section: Primary Contaminationmentioning
confidence: 99%
“…In South Korea, the prevalence of Salmonella Typhimurium is widely reported in the broiler and layer chicken farms or poultry products (Rayamajhi et al, 2010;Kim et al, 2012;Choi et al, 2014). Chickens infected with Salmonella Typhimurium appear asymptomatic, but continue to shed the pathogen for long periods of time, with rare cases of systemic disease (Wales & Davies, 2011). Human exposure to poultry or poultry products infected with Salmonella Typhimurium is a major risk factor for human infection (Cheong et al, 2007).…”
Section: Introductionmentioning
confidence: 99%